The Concept of Soul Education With ‘Tazkiyatun Nafs’ According Imam Al-Ghazali and Ibn Qayyim Al-Jauziyyah - Laode Muhammad Alfateh Arifin; Ilham Alsi; Hariyanto Hariyanto (At-Ta'dib, 2022)
Today, there are often irregularities in the educational process. This is due to a lack of attention on the issue of the planting of morals and character of students, which focuses only on physical and intellectual education regardless of the education of students. Therefore, researchers are interested in researching more about moral education known as Tazkiyatun Nafs. The researcher utilized the concept of Imam Al Ghazali & Ibn Qayyim Al Jauziyyah by analyzing the similarities and differences between the two. The type of research is library research. The main data of this study was the book of Ihya' Ulumuddin & Ar-Ruh. The data obtained is by using the documented method. While in its analysis researcher use descriptive methods, comparative methods, and core or content analysis methods. According to Imam Al Ghazali, Tazkiyatun Nafs is an effort to improve morality and mental medicine and animate life with Islamic values. Then, according to Ibn Qayyim al-Jauziyah, Tazkiyatun Nafs is purifying himself by infusing a good ubudiyah with ta'dib. The two figures share the same understanding of the concept of Tazkiyah as an attempt to draw closer to Allah Almighty and the need to plant ta'dib in each teaching process by example in education. The differences between the two include the application of the Tazkiyatun Nafs method; Imam Al Ghazali emphasized three aspects namely Tathahhur, Tahaqquq, and Takhalluk. And Ibn Qayyim al-Jauziyyah emphasized the three different; Al Ilm, Riyadhah, and Takhalluk.